Sistema para la Gestión de los Gases de Efecto Invernadero en el Banco Central de Costa Rica - Bolaños-Mejía, Ligia Elena (Instituto Tecnológico de Costa Rica, 2017)
In order to define a system for managing greenhouse gas emissions at the Central Bank of Costa Rica, its GHG emissions were quantified through the construction of an inventory based on the guidelines of ISO 14064:2016 for the year Natural 2015. Likewise, reduction measures, with performance indicators, were proposed for each of the emission sources. An economic assessment was made to ascertain the feasibility in the implementation of projects with high GHG reduction potential in the Bank's activities. A methodology for the monitoring of GHG was developed. The activities of the Central Bank produced 263.5 tons of CO2e during the year 2015. Of these, 43% is the product of emissions of one and two. The implementation of all the reduction measures will reduce 97 tons of CO2e and save 142 million colones per year to the BCCR. The measures with greater potential of reduction are the change of the vehicle fleet by electric vehicles, allowing to reduce the emissions coming from the consumption of gasoline. Similarly, the installation of photovoltaic panels, will reduce the consumption of electrical energy, reducing by 31% GHG emissions. The economic valuation showed profitability in the implementation of these projects. Hence, within a period of no more than 4 years will recover the investment of electric vehicles. Likewise, in a term not exceeding 5 years the BCCR could recover the investment made in the placement of the solar panels. Finally, the results demonstrate the value and importance, both economically and environmentally, of taking action on the business processes that generate GHG emissions.
Proyecto Final de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, Carrera de Ingeniería Ambiental, 2018.
Keywords: Cambio climático; Efecto invernadero; Gases de invernadero; Research Subject Categories::NATURAL SCIENCES::Earth sciences::Atmosphere and hydrosphere sciences::Climatology